Prognosis and acute complications at the first onset of idiopathic nephrotic syndrome in children: a nationwide survey in Japan (JP-SHINE study). Issue 3 (24th September 2019) - Sato, Mai; Ishikura, Kenji; Ando, Takashi; Kikunaga, Kaori; Terano, Chikako; Hamada, Riku; Ishimori, Shingo; Hamasaki, Yuko; Araki, Yoshinori; Gotoh, Yoshimitsu; Nakanishi, Koichi; Nakazato, Hitoshi; et al.
Abstract: Background: Information on the epidemiology of idiopathic nephrotic syndrome (INS) in children, complications of INS and the side effects of steroid therapy is scarce. Methods: The Japanese Pediatric Survey Holding Information of Nephrotic Syndrome, a nationwide cohort study, was conducted by the Japanese Study Group of Renal Disease in Children and enrolled 2099 children with newly diagnosed INS between 1 January 2010 and 31 December 2012. We conducted a follow-up study of the complications during the first onset and the patients' prognosis in this cohort. Results: We obtained follow-up data on 999 children (672 males) with a median age at onset of 4.5 years [interquartile range (IQR) 2.8–9.4] and a median follow-up period of 4.1 years (IQR 2.5–5.1). At the first onset, 24% of patients experienced severe acute kidney injury (AKI), defined as a serum creatinine increase to a level two or more times the baseline. On logistic regression analysis, age, hematuria, severe hypoalbuminemia (serum albumin <1.0 g/dL) and severe bacterial infection were not independent factors, but female sex {hazard ratio [HR] 1.5 [95% confidence interval (CI) 1.1–1.7]} and hypertension [HR 4.0 (95% CI 2.6–6.0)] were significantly related to AKI. During the observation period, ocular hypertension requiring treatment occurred in 17.4% of patients, among which 0.4% received surgical treatment. Progression to frequently relapsing nephrotic syndrome/steroid-dependent nephrotic syndrome in 3 years was seen in 44.2% of the patients and was shown by the Cox regression analysis to be significantly related to younger age and days until remission at the first episode, but not to sex, hematuria, the minimum serum albumin level or AKI. Two patients died during the observation period. One patient showed progression to end-stage kidney disease. Conclusion: Based on the results of a multicenter questionnaire survey, the overall survival and renal survival rates were found to be excellent. However, proper management of complications, particularly in AKI and ocular hypertension, is mandatory.